1998
DOI: 10.1016/s1074-7613(00)80577-4
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Compartmentation Is Required for Efficient T Cell Activation

Abstract: The plasma membrane of mammalian cells contains detergent-resistant membrane rafts enriched in glycosphingolipids and cholesterol. Although several important signaling molecules have been found in such rafts, evidence documenting a functional role for their localization has been scarce. Using a fractionation scheme that preserves tyrosine phosphorylation, we show that T cell activation leads to a striking compartmentation in the rafts of activated T cell receptor and associated signal-transducing molecules. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

51
802
0
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 869 publications
(857 citation statements)
references
References 88 publications
51
802
0
4
Order By: Relevance
“…However, there are points related to the potential mechanism which should be considered for future investigation. For example, rapid responses to external stimuli are facilitated by the organization of signaling molecules downstream of the TCR in distinct lipid rafts (15) leading to impairment of further stimulatory responses. Bcl-6 is essential for memory B cell development in germinal center (16).…”
Section: Memory Cd8 + T Cells Developed From Non-il-12-primed Effectomentioning
confidence: 99%
“…However, there are points related to the potential mechanism which should be considered for future investigation. For example, rapid responses to external stimuli are facilitated by the organization of signaling molecules downstream of the TCR in distinct lipid rafts (15) leading to impairment of further stimulatory responses. Bcl-6 is essential for memory B cell development in germinal center (16).…”
Section: Memory Cd8 + T Cells Developed From Non-il-12-primed Effectomentioning
confidence: 99%
“…Some reports have indicated that rafts play a critical role in TCR signalling. [24][25][26] These studies should, however, be viewed with caution as the amount of TCR/CD3 and their signal transducers recovered with rafts depends on the type of detergent used. 27 Recently, it was suggested that activation of Fas leads to the recruitment of FADD and caspase-8 into lipid rafts in mouse thymocytes, 28 human CD4 ĂŸ T cells 29 and in a human lymphoblastoid cell line, 30 indicating that such intracellular trafficking might also play a role in 'death receptor'-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…TCR signal transduction has been recently shown to be dependent on receptor recruitment to lipid rafts (Montixi et al, 1998;Xavier et al, 1998). These are detergent resistant plasma membrane microdomains highly enriched in cholesterol and glycosphingolipids, where key signaling molecules posttranslationally modiÂźed by addition of a lipid moiety, such Ras and Src family PTKs, reside (reviewed in Simons and Ikonen, 1997;Magee and Marshall, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These are detergent resistant plasma membrane microdomains highly enriched in cholesterol and glycosphingolipids, where key signaling molecules posttranslationally modiÂźed by addition of a lipid moiety, such Ras and Src family PTKs, reside (reviewed in Simons and Ikonen, 1997;Magee and Marshall, 1999). Following ligand binding, the activated TCR colocalizes in lipid rafts together with ZAP-70 and Syk, which are recruited to the tyrosine phosphorylated ITAMs from their otherwise cytosolic localization (Montixi et al, 1998;Xavier et al, 1998). Also the Shc adaptor inducibly localizes in the rafts following TCR triggering (Xavier et al, 1998), suggesting that raft localization might be required for Shc activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation